Faktor yang Berhubungan dengan Kejadian Dispepsia pada Pasien Rawat Inap di Rumah Sakit Umum Aliyah III Kota Kendari - Tri Afsari, Andi Monica; Sabilu, Yusuf; Mochtar, Febriana (NHM PRESS, 2023)
Dyspepsia is a syndrome of symptoms often found among the public characterized by pain or discomfort in the upper part of the solar plexus, nausea, bloating, belching, feeling full quickly, and feeling full in the stomach. This study aims to determine the factors associated with the incidence of dyspepsia in hospitalized patients at the Aliyah III general hospital in Kendari City. This type of research is quantitative, with an observational analytic method and a cross-sectional approach. This study used an accidental sampling technique with a total sample size of 68 patients. Data analysis using univariate and bivariate analysis using the chi-square test the results showed that the incidence of dyspepsia amounted to 58.8%, the level of stress in the severe category was 61.8%, the diet in the poor category was 58.8%, and the nutritional status in the normal category was 88.2%. The results of statistical tests using the chi-square test showed that there was a relationship between stress levels and dyspeptic (p = <0.05), there was a relationship between diet and dyspeptic (p = <0.05), and there was no relationship between nutritional status and dyspeptic (p = >0.05). The conclusion of this study is that the factors associated with the incidence of dyspepsia in hospitalized patients at Aliyah III Hospital in Kendari City are stress levels and diet. It is recommended that the hospital improve health services for patients by providing counseling about dyspepsia.